Association between multiple sclerosis and epilepsy: large population-based record-linkage studies - Allen, Alexander N (BMC Neurol, 2013)
BACKGROUND: Multiple sclerosis (MS) and epilepsy are both fairly common and it follows that they may sometimes occur together in the same people by chance. We sought to determine whether hospitalisation for MS and hospitalisation for epilepsy occur together more often than expected by chance alone. METHODS: We analysed two datasets of linked statistical hospital admission records covering the Oxford Record Linkage Study area (ORLS, 1963–1998) and all England (1999–2011). In each, we calculated the rate of occurrence of hospital admission for epilepsy in people after admission for MS, compared with equivalent rates in a control cohort, and expressed the results as a relative risk (RR). RESULTS: The RR for hospital admission for epilepsy following an admission for MS was significantly high at 4.1 (95% confidence interval 3.1–5.3) in the ORLS and 3.3 (95% CI 3.1–3.4) in the all-England cohort. The RR for a first recorded admission for epilepsy 10 years and more after first recorded admission for MS was 4.7 (2.8–7.3) in ORLS and 3.9 (3.1–4.9) in the national cohort. The RR for the converse–MS following hospitalisation for epilepsy–was 2.5 (95% CI 1.7–3.5) in the ORLS and 1.9 (95% CI 1.8–2.1) in the English dataset. CONCLUSIONS: MS and epilepsy occur together more commonly than by chance. One possible explanation is that an MS lesion acts as a focus of an epileptic seizure; but other possibilities are discussed. Clinicians should be aware of the risk of epilepsy in people with MS. The findings may also suggest clues for researchers in developing hypotheses about underlying mechanisms for the two conditions.